Luciferase Detection during Stationary Phase in Lactococcus lactis - Bachmann, Herwig (American Society for Microbiology, 2007)
The luminescence signal of luxAB-encoded bacterial luciferase strongly depends on the metabolic state of the host cell, which restricts the use of this reporter system to metabolically active bacteria. Here we show that in stationary-phase cells of Lactococcus lactis, detection of luciferase is significantly improved by the addition of riboflavin or flavin mononucleotide to whole-cell assay systems.